A history of conversion to Islam in the United States / Volume 1 White American muslims before 1975 - Bowen, Patrick D. (A history of conversion to Islam in the United States, 2015)
Preliminary Material -- Introduction -- From Renegades to Transcendentalists -- The Occult Revival -- The Makings of a Muslim Missionary -- Islamophilic Masonry -- The Rise and Fall of a Brotherhood -- The Post-Movement Years -- The Non-Orthodox Transition -- New Bonds -- Uniting Muslim Communities -- The Postwar Shift -- Reorientation -- Conclusion -- Bibliography -- Index.